Electronic load controller in pico hydro power system / Mohd Fais Md Nooh - Md Nooh, Mohd Fais (2013)
This paper describes the design and development of a prototype of an uncontrolled turbine in pico hydro power generation with constant input power. This system produces small output power not exceeding thirty (30) watts. A water wheel turbine was used to spin rotor of alternator. The alternator converted kinetic energy into electrical energy.